Saving and Investment: Final Comment - Lutz, F. A. (Quarterly Journal of Economics, 1939)
Journal Article Final Comment Get access F. A. Lutz F. A. Lutz Princeton University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 53, Issue 4, August 1939, Pages 627–631, https://doi.org/10.2307/1883283 Published: 01 August 1939